2016
DOI: 10.1007/s12520-016-0398-9
|View full text |Cite
|
Sign up to set email alerts
|

Eating out or dining in: modeling diverse dietary strategies in the Middle Period, San Pedro de Atacama, Chile

Abstract: The Middle Period of the Atacama oases, North Chile, has been characterized as a time of peace, uniform abundance, and widespread access to exotic materials. In the present work, we test this notion through a comparison of Middle Period human isotopic data (δ 13 C co , δ 15 N co , and δ 13 C ap ) representing two distinct ayllus, Solcor and Tchecar, in the San Pedro de Atacama oases. We employ Bayesian mixture modeling of individual-level isotopic data to quantify and compare dietary composition within and bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…However, the inland sites of the Formative, Middle Horizon, and Late‐Intermediate period are characterized by very variable in utero increment values. Their wide‐ranging δ 15 N and δ 13 C values probably derive from the dietary heterogeneity seen in the adults during these time periods (King et al, ; Pestle et al, ; Santana‐Sagredo, Lee‐Thorp, et al, ; Santana‐Sagredo, Uribe, et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the inland sites of the Formative, Middle Horizon, and Late‐Intermediate period are characterized by very variable in utero increment values. Their wide‐ranging δ 15 N and δ 13 C values probably derive from the dietary heterogeneity seen in the adults during these time periods (King et al, ; Pestle et al, ; Santana‐Sagredo, Lee‐Thorp, et al, ; Santana‐Sagredo, Uribe, et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…We sampled individuals from all archaeological periods, due in part to knowledge that preservation of collagen in early periods is variable (King et al, ). Previous isotopic work has also indicated that agricultural staples, such as maize, played a variable part in the adult diet through time (King et al, ; Pestle, Torres‐Rouff, Hubbe, & Smith, ; Santana‐Sagredo, Hubbe, & Uribe, ; Santana‐Sagredo, Lee‐Thorp, Schulting, & Uribe, ; Santana‐Sagredo, Uribe, Herrera, Retamal, & Flores, ), and it is likely that this variation also extends to childhood diet. By sampling widely, and including later archaeological phases, we increase the likelihood of identifying complementary feeding using maize, and the possibility of seeing changes to stress levels through time.…”
Section: Methodsmentioning
confidence: 97%
“…However, there are significant differences between cemeteries in the prevalence of traumatic injury. Our recent bioarchaeological research in concert with evidence for the long use life of these cemeteries (e.g., Hubbe et al, ; Pestle, Torres‐Rouff, & Hubbe, , Pestle, Torres‐Rouff, Hubbe, & Smith, ; Torres‐Rouff & Hubbe, ) has suggested that the cemeteries in the oases do not necessarily represent a single social group or status. We argue that they might more accurately reflect complex kin and political groupings in sync with our understanding of the ayllu , the traditional form of Andean kin‐based community structure.…”
Section: Coyo Oriental and The Atacameño Oases During The Middle Periodmentioning
confidence: 97%
“…This multisource mixture modeling technique is one of several developed with the hope of better bounding estimates of food source contribution. Indeed, recent southern Andean attempts (Andrade et al, ; Pestle et al, ; Pestle, Torres‐Rouff, & Hubbe, ; Pestle, Torres‐Rouff, Hubbe, & Smith, ) at modeling have tended to use this, or similar, Bayesian approaches, which accommodate underdetermined systems (those with more than n + 1 sources), and also allow for the incorporation of priors (Fernandes et al, ; Moore & Semmens, ; Parnell, Inger, Bearhop, & Jackson, ). These approaches “offer a powerful means to interpret data because they can incorporate prior information, integrate across sources of uncertainty and explicitly compare the strength of support for competing models or parameter values,” (Moore & Semmens, : p. 471).…”
Section: Methodsmentioning
confidence: 99%